Note on Australian Triplectidinae (Trichoptera: Leptoceridae). - Neboiss, Arturs (Contributions to Entomology = Beiträge zur Entomologie, 1957)
Re-examination of the male and female type specimens of Triplectides australis Navâs showed that they belong to two different species. The male specimen is referred to Hudsonema maculata Mosely, but the female remains unchanged as Triplectides australis Navâs. The discovery of young larvae inside the body of the female is the first indication of viviparous Trichoptera in Australia. Another four specimens of Triplectides australis Navâs carrying larvae have since been discovered from Queensland. Figures are given for both species. Nomenclatural Acts australis (female) Navás, 1934 (Triplectides), bona spec. australis (only male) Navás, 1934 (Triplectides), misidentification of Hudsonema maculata Mosely, 1953